ANALISIS KEWAJARAN OPINI LAPORAN AUDITOR PADA BANK TAPIN: STUDI DATA SEKUNDER - Noor Syifa Rahmah; Monika Handayani (P3M Politeknik Negeri Banjarmasin, 2024)
This study aims to analyze the fairness of auditor opinions on the financial statements of Bank Tapin using secondary data. Auditor opinions serve as an important indicator in assessing the transparency and fairness of a company's financial statements, particularly in the banking sector, which plays a significant role in the economy. In this study, the data used include the annual financial statements of Bank Tapin as well as the independent auditor's reports published during the period. The analysis is conducted by comparing the auditor opinions issued with the auditing standards applicable in Indonesia, namely SA (Standar Audit), to evaluate whether the opinions provided reflect fairness in accordance with generally accepted accounting principles. The results of the study indicate that the auditor's opinion for Bank Tapin during the analyzed period is unqualified, suggesting that the financial statements presented meet the criteria for fairness and transparency. This research is expected to contribute to the development of auditing practices in the banking sector and enhance understanding of the importance of auditor opinions in maintaining public trust in the financial stability of banks.